Essays on economics of mental health - Salokangas, Henri R.W. (fi=Turun yliopisto|en=University of Turku|, 2020)
This dissertation consists of an introductory chapter and three empirical essays that examine the linkages between economic activity and mental disorders. I examine two separate themes: the effect of migration on long-term mental health and the association of mental disorders and labor market performance. The first article of the thesis exploits a historical natural experiment in forced migration in the World War II to study the impact of migration on mental health. The Finnish-Soviet wars resulted in the displacement of 11% of the Finnish population. As the forced migration of Finnish Karelians was unexpected and was conducted with full compliance, the displacement provides a compelling “naturalexperiment” framework to study the mental health effects of forced migration free on confounding. We do not find evidence that supports migration being a risk factor for mental disorders in the long-term. This result is at odds with the general finding from non-experimental studies that point to a positive association between migration and mental disorders. Our results highlights the importance of an appropriate research design when measuring the impacts of migration. The second article examines the lifetime labor market consequences of mental disorders. The main contribution stems from the scope of the data, which allows the identification of the emergence of severe mental disorders as the first psychiatric admission. By documenting that, the labor market deficits are the greater the earlier the mental health problems manifest, the paper motivates the need for early intervention to tackle these problems. The third article focuses more closely on the immediate changes in labor market performance surrounding the first psychiatric admission. I exploit a recently popularized dynamic differences-in-differences strategy where counterfactuals are constructed from amongst the individuals with psychiatric admissions, but who are just treated for the first time a few years later than the treatment group. I show that this way the observable differences between treatment and control group are considerably reduced relative to case-control comparison. This strategy also produce results that do not violate the parallel trends assumption in anxiety disorders.

Esseitä mielenterveydestä ja taloudellisesta toiminnasta Tämä väitöskirja koostuu johdantoluvusta sekä kolmesta esseestä, jotka tarkastelevat taloudellista toimintaa ja mielenterveyshäiriöitä. Tarkastelu jakautuu kahteen aihepiiriin: muuttoliikkeen pitkän aikavälin mielenterveysvaikutuksiin sekä mielenterveyshäiriöiden yhteydestä työmarkkinamenestykseen. Ensimmäisessä väitöskirjatutkimuksessani tarkastelen pakkosiirtolaisuuden pitkän aikavälin vaikutuksia mielenterveysongelmiin. Suomen ja Neuvostoliiton välillä käydyt sodat tarkoittivat sitä, että Neuvostoliitolle luovutetuilla asunut Suomen väestö tuli uudelleenasuttaa muualle Suomeen. Hyödynnämme Luovutetun Karjalan väestön pakkosiirtolaisuutta ns. ”luonnollisena kokeena”, joka mahdollistaa muuttoliikkeen mielenterveysvaikutusten tutkimisen ilman muuttoliikkeeseen tyypillisesti liittyvää valikoitumisharhaa. Aiemmista tutkimuksista poiketen emme havaitse muuttoliikkeen olevan yhteydessä kohonneeseen pitkän aikavälin mielenterveyshäiriöriskiin. Tutkimuksemme havainnollistaa tutkimusasetelman merkitystä muuttoliikkeeseen liittyvissä vaikutusarvioinneissa. Toisessa paperissani tarkastelen mielenterveyshäiriöiden yhteyttä elinajan työmenestykseen. Tutkimus hyödyntää aiempaa kattavammin suomalaista rekisteriaineistoa, joka mahdollistaa ensimmäisten psykiatristen hoitokäyntien tunnistamisen. Tutkimuksessa havaitaan, että työuran työmarkkinamenestys on sitä heikompaa mitä aikaisemmin sairastuu vakavaan mielenterveyshäiriöön. Tämä havainto kannustaa arvioimaan psykiatristen varhaisten interventioiden vaikutusta myös taloudellisesta näkökulmasta. Kolmannessa paperissani tarkastelen vakavien mielenterveysongelmien välitöntä yhteyttä työmarkkinamenestykseen. Hyödynnän tutkimuksessa dynaamista differences-in-differences -tutkimusasetelmaa, jossa sairastuneita verrataan muihin muutamaa vuotta myöhemmin sairastuneisiin. Havainnollistan, että tämänkaltainen vertailu vähentää valikoituvuusongelmaa suhteessa tyypilliseen tapausverrokkiasetelmaan sekä täyttää yhtenevien trendien oletuksen ahdistuneisuushäiriöissä.